Theoretical and experimental investigations of transient flow in oil-hydraulic small-diameter pipe system. (October 2021) - Urbanowicz, Kamil; Stosiak, Michał; Towarnicki, Krzysztof; Bergant, Anton
Highlights: The numerical simulations were carried out in one-dimensional space, so the calculating time is close to the actual duration of the investigated phenomenon. The rational control of the valves significantly counteracts overloads which occur during fluid hammer. Control optimization will contribute to cost savings in newly designed systems, since it will no longer be necessary to use specialist devices limiting the negative effects of fluid hammer. The accuracy of the simulation model can be further increased by taking into account pump delivery fluctuations. Abstract: This paper investigates unsteady flow phenomena in a new oil-hydraulic small-diameter pipeline apparatus at the Wrocław University of Science and Technology, Poland. The steel pipe section lengths can be either 2 or 7 m, and the internal pipe diameter 4 mm (micro-hydraulic system). Transient event was triggered by a rapid closure of a downstream end bi-directional poppet valve. Pressures and velocities were investigated at the pipe end points. The main objective was to investigate effects of valve action on pressure magnitudes and timing in a number of transient laminar flow situations. In the method of characteristics numerical simulations a quasi-steady and a novel computationally effective Urbanowicz's convolution-based unsteady friction models were used, as well as a quadratic bi-directional poppet valve function boundary condition. Comparisons between measured and calculated results clearly show that the valve closure path and the unsteady friction control the effects of unsteadiness on attenuation, shape and timing of pressure pulses in a small-diameter pipeline system; however, the unsteady friction is less important for the cases characterized by a relatively large fluid hammer number.